2020
DOI: 10.3390/v12010076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Provides Molecular Insights into the Interaction of Beet necrotic yellow vein virus and Beet soil-borne mosaic virus with Their Host Sugar Beet

Abstract: Beet necrotic yellow vein virus (BNYVV) and Beet soil-borne mosaic virus (BSBMV) are closely related species, but disease development induced in their host sugar beet displays striking differences. Beet necrotic yellow vein virus induces excessive lateral root (LR) formation, whereas BSBMV-infected roots appear asymptomatic. A comparative transcriptome analysis was performed to elucidate transcriptomic changes associated with disease development. Many differentially expressed genes (DEGs) were specific either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“…Our findings revealed that BNYVV infection induced ethylene biosynthesis but repressed GA signal pathway in the infected N. benthamiana leaves, consistent with the results from transcriptome analysis of BNYVV-infected N. benthamiana leaves reported previously [10]. However, Fernando Gil et al reported that the ethylene signal transduction pathway is strongly suppressed in the BNYVV-infected root tissues of sugar beet [11], and neither B. macrocarpa nor B. vulgaris was reported to show changes in the genes of the GA signal pathway during BNYVV-infection [7,11,12]. Instead, the auxin response is predominantly regulated in both B. macrocarpa and B. vulgaris during BNYVV infection [7,11,12], suggesting plant-species-specific hormonal responses to BNYVV.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings revealed that BNYVV infection induced ethylene biosynthesis but repressed GA signal pathway in the infected N. benthamiana leaves, consistent with the results from transcriptome analysis of BNYVV-infected N. benthamiana leaves reported previously [10]. However, Fernando Gil et al reported that the ethylene signal transduction pathway is strongly suppressed in the BNYVV-infected root tissues of sugar beet [11], and neither B. macrocarpa nor B. vulgaris was reported to show changes in the genes of the GA signal pathway during BNYVV-infection [7,11,12]. Instead, the auxin response is predominantly regulated in both B. macrocarpa and B. vulgaris during BNYVV infection [7,11,12], suggesting plant-species-specific hormonal responses to BNYVV.…”
Section: Discussionsupporting
confidence: 92%
“…However, Fernando Gil et al reported that the ethylene signal transduction pathway is strongly suppressed in the BNYVV-infected root tissues of sugar beet [11], and neither B. macrocarpa nor B. vulgaris was reported to show changes in the genes of the GA signal pathway during BNYVV-infection [7,11,12]. Instead, the auxin response is predominantly regulated in both B. macrocarpa and B. vulgaris during BNYVV infection [7,11,12], suggesting plant-species-specific hormonal responses to BNYVV. Notably, auxin increased considerably in sugar beet roots after BNYVV infection [11,12], whereas in the leaves of B. macrocarpa, the auxin response seems to be repressed, as evidenced by the upregulations of miR393 and consequent down-regulation of transport inhibitor response protein 1 [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations